A bibliometric review on deoxyribonucleic acid (DNA) splicing system - Nooradelena, Mohd Ruslim; Yuhani, Yusof; Mohd Sham, Mohamad; Mudaber, Mohammad Hassan (Penerbit Akademia Baru, 2024)
This study objects to provide a communicative review for splicing system, focusing on deoxyribonucleic acid (DNA) published in journals and proceedings indexed by the Scopus database. The method of bibliometric analysis is used to describe and analyze the evolution of publication structure and its various co-relationships such as citation, co-citation, co-authorship, and co-occurrence, among the chosen 174 documents indexed by Scopus. This study gives some insightful direction of research where the most influential documents and authors were determined. Besides, the emerging of technologies in most of the research works conducted previously promote the hybridization of background of studies specifically in mathematics, biology, and computer science. The study is limited to English articles which was published by the Scopus database, ranging from the year of 1983 until 2023. The source is also limited to Scopus journals and proceedings only. As far as the authors are aware, this is the first study to address the splicing system topic from a bibliometric perspective. The authors believe that this bibliometric review will help scholars and researchers to stand firm bases regarding the scientific development of this field of study.